The impact of the quality of electronic services on the satisfaction of service recipients (Journal of the College of Basic Education, 2022)
The study aims to find out the effect of the quality of the electronic form provided by the Iraqi Commission for Computers and Informatics on the satisfaction of the service recipients, by measuring the research for the dimensions of the explanatory variables and their impact on the dependent variable. In order for the research to achieve its goal, a questionnaire was developed for the purpose of data collection. Business Administration